The energy cost of polypeptide knot formation and its folding consequences - Bustamante A. (2017)
This work was supported by Fondecyt 11110534 (to M.B.), 1151274 (to M.B.), 11130263 (to C.A.M.W.), Anillo 1107 (to M.B.), and Chile and Fondecyt 196–2013 (to D.G.G.) CONCYTEC, Perú. This research was partially supported by the supercomputing infrastructure of the NLHPC (ECM-02) at Universidad de Chile. A.B. was supported by Conicyt master fellowship 22121199. We gratefully acknowledge Professor Alexander Vologodskii from New York University for helpful comments and advice. Travel for C.B. to and from Chile and Peru was also partially supported by the Howard Hughes Medical Institute, NIH grant R01GM032543, and the U.S. Department of Energy Office of Basic Energy Sciences Nanomachine Program under contract no. DE-AC02-05CH11231.